Analysis of Battery Technologies for Use as Battery Management Systems in a Simple Solar Power Plant - Rudi, Syahputra; Nelly, Safitri; Yassir, .; Teuku, Hasannuddin; Taufik, . (INTI International University, 2024)
A solar power plant is a device that uses solar radiation to generate electricity. However, a dependable energy storage system is essential to effectively operating solar power plants. This study aims to examine how battery technology is used in solar power plants as a voltage storage. Specifically, the performance of lithium-ion and lead acid batteries, known as valve-regulated lead acid (VRLA), will then be compared. The findings demonstrate that Lithium-ion Batteries are better at keeping a steady voltage in no-load situations. The highest voltage value was recorded at 13:79 V at a 90° tilt angle and 13:00 Indonesia time. At the same hour, the VRLA Battery recorded the lowest voltage of 12.08 V with a 0° tilt angle. Under load conditions, the Lithium-ion Battery performed better with a more moderate voltage drop, achieving the lowest voltage of 12.68 V at an inclination angle of 165° and 14:00 Indonesia time, compared to the VRLA Battery's lowest value of 12.08 V under comparable conditions. Thus, Lithium-ion Batteries are thought to be more efficient and stable than VRLA Batteries in solar power plant applications, particularly in terms of voltage stability under changing operating conditions. Furthermore, battery selection should still take into account the initial investment cost and the unique requirements of the solar power plant system to be deployed.